External Ventricular Drains: Development and Evaluation of a Nursing Clinical Practice Guideline - Tainara Wink Vieira; Victória Tiyoko Moraes Sakamoto; Bárbara Rodrigues Araujo; Daiane Dal Pai; Carine Raquel Blatt; Rita Catalina Aquino Caregnato (MDPI AG, 2022)
External ventricular drains (EVDs) are common in intensive care for neurocritical patients affected by different illnesses. Nurses play an essential role to ensure safe care, and guidelines are tools to implement evidence-based care. Thus, the aim of this study was to develop and evaluate the quality of a clinical guideline for critically ill patients with EVDs. Methodological research was conducted. The guideline development was based on a scoping review about nursing care to patients with EVDs. The guideline evaluation occurred in two phases: evaluation of its methodological rigor, with application of the Appraisal of Guidelines Research and Evaluation II to four experts on guidelines evaluation; and the Delphi technique, with a panel of nine specialists in neurocritical care, performed in two rounds. Data were analyzed by descriptive statistics and content validity ratio. In the first phase of the evaluation, three domains did not reach consensus, being reformulated. The second phase was conducted in two rounds, with nine and eight participants respectively, with 13 recommendations being reformulated and reassessed between rounds, inclusion of an EVD weaning category, and two flowcharts on patient's transport and mobility. Therefore, the guideline can be incorporated into nursing care practices. Further studies are necessary to assess its impact on clinical practice.